2017
DOI: 10.1038/s41598-017-00811-7
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of distraction and conflict resolution for nonverbal auditory events

Abstract: In everyday situations auditory selective attention requires listeners to suppress task-irrelevant stimuli and to resolve conflicting information in order to make appropriate goal-directed decisions. Traditionally, these two processes (i.e. distractor suppression and conflict resolution) have been studied separately. In the present study we measured neuroelectric activity while participants performed a new paradigm in which both processes are quantified. In separate block of trials, participants indicate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…As previously found with the TAiL paradigm (Stewart et al, 2017;Zhang et al, 2012), listeners showed a stronger effect of involuntary orienting on RTs in the attend-frequency task than in the attend-location task. Meanwhile, the effect of conflict resolution on RTs was comparable between the two TAiL tasks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously found with the TAiL paradigm (Stewart et al, 2017;Zhang et al, 2012), listeners showed a stronger effect of involuntary orienting on RTs in the attend-frequency task than in the attend-location task. Meanwhile, the effect of conflict resolution on RTs was comparable between the two TAiL tasks.…”
Section: Discussionsupporting
confidence: 83%
“…Behavioral studies using TAiL provide support that the task taps into these two attentional constructs of involuntary orientation and conflict resolution using auditory stimuli (Stewart & Amitay, 2015;Zhang et al, 2012). Using scalp recordings of ERPs, Stewart, Amitay, and Alain (2017) showed distinct ERP modulations associated with involuntary orienting and conflict resolution. The comparison of distributed source analyses for involuntary orienting suggests a more dorsal source when the taskirrelevant sound feature was location than when it was frequency.…”
Section: Introductionmentioning
confidence: 94%
“…Meanwhile our auditory results show additional 423 dorsal pathway areas were recruited for spatial conflict resolution. Furthermore, our ERP study 424 (Stewart et al, 2017) showed that while both TAiL tasks had earlier onsets of conflict resolution 425 processing compared to similar visual studies, the auditory spatial task had an additional negative 426 frontocentral component with timings straddling both auditory and visual Stroop tasks. Together 427 with our fMRI findings, this suggests that resolving conflict in auditory spatial tasks is more Our finding is in contrast to the findings of Haupt and colleagues (Haupt,Axmacher,430 Cohen, Elger, & Fell, 2009) who found that non-spatial auditory conflict resolution required 431 more activation in the very posterior part of the ACC than spatial auditory conflict resolution.…”
Section: Comparisons 400mentioning
confidence: 62%
“…However, the timelines and 462 how these pathways are facilitated with regards to specific attention constructs differ between the 463 domains. Auditory involuntary orienting and conflict resolution have been found to occur faster 464 than visual involuntary orienting and conflict resolution (Stewart et al, 2017). The results from 465 this current study suggest that additional dorsal pathway cortical areas are recruited for auditory 466 spatial attention constructs.…”
Section: Conclusion 459mentioning
confidence: 65%
“…Prior work in the visual domain has shown that the P3a/Pd is elicited in response to confusable distractors that share features similar to the target (Hickey et al, 2009;Hilimire et al, 2011;Sawaki and Luck, 2010). Similarly, auditory EEG studies found that this ERP component was elicited when listeners were distracted by a change in task-irrelevant features of a sound (e.g., Goldstein et al, 2002;Gaeta et al, 2003;Stewart et al, 2017). Thus, we expected to observe a P3a-like evoked response to mixed talkers' speech if listeners' attentional focus is disrupted by changes in task-irrelevant acoustic features, such as those that occur when the talker switches.…”
Section: Introductionmentioning
confidence: 94%